The treatment efficacy of three-layered functional polymer materials as drug carrier for orthotopic colon cancer - Zhuo Liu; Dongxin Wang; Qian Cao; Jiannan Li (Taylor & Francis Group, 2022)
Colorectal cancer (CRC) is a worldwide disease posing serious threats to people's life. Surgery and postsurgical chemotherapy are still the first choices to control the rapid progression of cancer. However, tumor recurrence and even distant metastasis are prone to occur. As a result, it is in urgent demand to find a new method to control CRC progression while inhibiting distant metastasis. On this basis, this study developed the three-layered functionalized hydrogel-fibrous membrane-hydrogel composite materials. The Chinese traditional drugs 20 (S)-ginsenoside Rg3 (Rg3) and chemotherapeutic agent 5-fluorouracil (5-Fu) were loaded in the inner hydrogel and middle fibrous membrane and could be constantly released at the same time and space. The outer hydrogel was decorated with phenylboronic acid (PA) to interact with sialic acid expressed on the CRC cell surface. The composite materials possessed biocompatibility and showed no toxicity to normal human intestinal mucosa endothelial cells HIEC. According to the results, the cell viability of CT26 could be significantly decreased in vitro. The three-layered functionalized materials inhibited the original tumor progression and distant tumor metastasis to the liver in an orthotopic colon cancer mouse model by increasing the caspase3 expression and inhibiting the expressions of Bcl-2, Ki-67, and VEGF. In addition, the functions of major organs were not significantly damaged. Our study provides a safe and efficacious method of this three-layered functionalized hydrogel-fibrous membrane-hydrogel composite materials for CRC treatment.